Law, legislature, and judiciary - Varma, Umeshwar Prasad (New Delhi, India : Mittal Publications, 1996)
With reference to India.
Keywords: Constitutional law -- India; Separation of powers -- India; Judicial power -- India; Law -- Political aspects